Hubungan Motivasi dengan Perilaku Ibu Post Partum dalam Melakukan Mobilisasi Dini - Ferilia Adiesti (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
Bleeding Post-delivery is one of the causes of death in the mother. Which is the most common cause of postpartum bleeding is 50-60% due to muscle weakness or absence of uterine contractions. This can be caused because post partum mothers do not carry out early postpartum mobilization in the first 24 hours after labor and the following days. Analytical design - cross sectional. The number of samples was 28 people and the sampling technique was consecutive sampling. The independent variable is the motivation of post partum mothers to do early mobilization, while the dependent variable is the behavior of post partum mothers in conducting early mobilization, collecting data using a questionnaire. Based on the results of the study that more than 50% of respondents (60%) were not motivated in conducting early mobilization, at most the behavior of post partum mothers doing early mobilization was less than 12 people (48%). The Wilcoxon test results showed that α was smaller than α table is 0,000 <0,05, meaning that there is a relationship between motivation and maternal behavior in carrying out early mobilization. It is expected that midwives can provide information about early mobilization by applying directly and also helping post partum mothers in early mobilization so that post partum mothers are not afraid to carry out early mobilization.